(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
Political conflict between the Pattani Malays and the Thai government dates back to the 16th century. The "siamisation" policy intensified this conflict. Since then, despite several attempts to resolve this situation, whether through military action or negotiation, have been made and yet all efforts to end this conflict have failed. The approaches to end the conflict have undergone modifications in line with the demands of time and circumstance. Today, the conflict has entered a new phase whereby the new media has become a mechanism for both parties to give their views on the conflict. What are the issues being discussed in the new media? What are the strategies used to influence this wide and varied audience? This research is based on web studies, i.e. a textual analysis combining discursive and rhetorical as well as cultural analysis. The study finds that views concerning history, violence, death, hatred, and economic as well as social destruction as a result of the conflict are aired on the websites and blogs studied in this research. Views concerning the political conflict between the Pattani Malays and the Thai authorities are presented using the rhetorical strategies employing the rhetorical devices pathos, ethos and logos. Keywords: political conflict; Pattani Malays; web studies; rhetorical strategies